Quality enhancement of microstructure and surface topography of NiTi parts produced by laser powder bed fusion. (November 2020) - Khademzadeh, S.; Zanini, F.; Rocco, J.; Brunelli, K.; Bariani, P.F.; Carmignato, S.
Abstract: Laser powder bed fusion (LPBF) is a robust metal additive manufacturing technique for generation of complex geometries using a high-energy laser beam. NiTi is a promising material for porous biomaterials applications. The use of LPBF for such applications is justified by the complex architecture of porous biomaterials and by the current difficulties in NiTi manufacturing. Elimination of unwanted secondary phases after LPBF of NiTi has been an important research topic in recent years. In this research work, the effect of LPBF process parameters on phase composition, porosity, and surface topography of NiTi parts has been studied using different techniques, including X-ray diffraction, scanning electron microscopy and micro X-ray computed tomography. Three different regimes of process parameters have been proposed for obtaining the single phase B2-NiTi by LPBF technique. The obtained results revealed that high laser power adjusted to high scanning speed reduced the surface roughness and the porosity content in LPBF NiTi products.